COVID-19 vs. stakeholder engagement: the impact of coronavirus containment measures on stakeholder involvement in European energy research projects [version 3; peer review: 2 approved] - Diana Süsser; Andrzej Ceglarz; Vassilis Stavrakas; Johan Lilliestam (Open Research Europe, 2021)
The coronavirus (COVID-19) pandemic has affected societies and economies around the world, and the scientific community is no exception. Whereas the importance of stakeholder engagement in research has grown quickly the consequences of the pandemic on this has so far not been empirically studied. In this paper, we investigate the effects of the COVID-19 crisis on European energy research, in particular the stakeholder work, during the first wave of the coronavirus in spring and summer 2020. We pose the research questions: (i) How much of a problem are the coronavirus containment measures for stakeholder engagement? (ii) How have researchers coped with the situation, and (iii) How do they evaluate alternative stakeholder activities implemented? We conducted an online survey among European energy research projects with stakeholder engagement between June and August 2020. We found that only one of six engagement activities could be implemented as planned, whereas almost half were cancelled or delayed. The most common coping strategies were changing involvement formats – mainly to webinars or online workshops – or postponement. Whereas respondents are largely satisfied with one-to-one and unidirectional online formats, such as webinars, online interviews, and online surveys, they see interactive group activities as less suitable for online engagement. Most respondents plan to continue using online formats to complement, but not to replace, physical meetings in future research. All long-term effects remain to be seen, but given the postponement of many stakeholder involvement activities, many projects may face problems at later stages of their realisation. These findings suggest that the pandemic may have catalysed a rapid introduction of specific online formats in academic stakeholder interaction processes.